The place of thalidomide in the treatment of multiple myeloma - Alessandro Corso; Silvia Mangiacavalli (Oncology Reviews, 2011)
Thalidomide represents the first attempt in multiple myeloma (MM) patients to overcome resistance to chemotherapy through a biological agent. The exciting results reported in the first study by Singhal et al. in 1999 [1] led to several other studies which aimed to evaluate its efficacy in different settings and disease phases, to define its toxicity, and to establish the optimal dose. Some of these questions have already been answered while others, such as the best dosage or the best schedule to obtain the highest efficacy with the lowest toxicity, still remain. Thalidomide has been studied as a single agent or in association with other drugs (dexamethasone, chemotherapy and new drugs) showing a synergic activity. We review the results of the main studies on the efficacy and toxicity of thalidomide used as a single agent or in association with other drugs, reflect on its present role, and consider its future contribution to the treatment of MM.